Fish Meal Potential Test of Fish Waste from Traditional Markets in Tanjungpinang City as an Alternative Raw Material for Feed of Marine Fish Culture: Fish Meal (Jurnal Intek Akuakultur, 2019)
This study purpose to find out local alternative raw materials to reduce the use of imported fish meal in the formulation of feed production for fish culture. The potential test of fish waste (head and bone) of lemuru (Sardinella lemuru) was through the proximate test of nutritional content including water, ash, protein, fat, crude fiber, and carbohydrate. Proximate analysis for water content by heating in an oven at a temperature of 105-110 oC, ash content by heating in a furnace with a temperature of 600 oC, protein was carried out by Kjeldahl method, fat was carried out using Soxhlet method, crude fiber using a sample dissolution method with strong acids and bases and heating . The results showed fish waste (head and bone) of lemuru can produce fish meal with 40.68Â±0.42% protein content.